Analysis and interpretation of ethnographic data : a mixed methods approach - LeCompte, Margaret Diane (Ethnographer's toolkit, 2013)
Analysis and Interpretation of Ethnographic Data: A Mixed Methods Approach, Second Edition, is a comprehensive treatment of analysis strategies used inethnographic research, addressing the "crunching" and manipulation of bothqualitative and quantitative ethnographic data.